Development of a mouse embryonic stem cell model for investigating the functions of the linker histone H1-4 - Abu Alhaija, Abed Alkarem; Lone, Imtiaz Nisar; Sekeroglu, Esin Ozkuru; Batur, Tugce; Angelov, Dimitar; Dimitrov, Stefan; Hamiche, Ali (Wiley, 2024)
The linker histone H1 C-terminal domain (CTD) plays a pivotal role in chromatin condensation. De novo frameshift mutations within the CTD coding region of H1.4 have recently been reported to be associated with Rahman syndrome, a neurological disease that causes intellectual disability and overgrowth. To investigate the mechanisms and pathogenesis of Rahman syndrome, we developed a cellular model using murine embryonic stem cells (mESCs) and CRISPR/Cas9 genome engineering. Our engineered mES cells facilitate detailed investigations, such as H1-4 dynamics, immunoprecipitation, and nuclear localization; in addition, we tagged the mutant H1-4 with a photoactivatable GFP (PA-GFP) and an HA tag to facilitate pulldown assays. We anticipate that these engineered cells could also be used for the development of a mouse model to study the in vivo role of the H1-4 protein.
Keywords: cellular model; CRISPR/Cas9; H1.4; linker histones; mES cells; Rahman syndrome